Kajian Identifikasi Jenis Flora dan Kelimpahannya di Lahan Penetapan Taman Keanekaragaman Hayati Kelurahan Karangasem, Kecamatan Ponjong, Kabupaten Gunung Kidul - Yuslinawari Yuslinawari; Doris Doris; Sugeng Wahyudiono (Journal of People, Forest and Environment, 2021)
ABSTRACTFlora as an element of the ecosystem that can provide biodiversity is a major element in the conservation of forest resources. Biodiversity has 3 levels, namely ecosystem, species and genetic diversity. In identifying the abundance of flora in the biodiversity park in Gunung Kidul Regency, the aim is to obtain preliminary data before artificial intervention is carried out to maintain the succession to achieve flora abundance. This biodiversity park also has a specialization to maintain the diversity of the ecosystem level because it is in the form of limestone / karst land which is a variety of habitats along with biotic communities and ecological processes. This study used a 100% census method with a stratified sampling unit. The area of land studied was 3 ha with direct observation method by giving yellow paint for the observed flora.The results of vegetation identification showed that the types of flora in 2019 were 21 species. This species has a total of 1908 individuals. Diversity index data (H ') is 1.15 so it is said to have low diversity. While the wealth index (R ') with a value of 2.67 and is included in the medium type wealth range. The evenness index value (E ') with a value of 0.37 makes the information about the biodiversity garden land has an uneven distribution of flora.This initial parameter provides a form of data for the management of Taman Biodiverstity Park by paying attention to the structure and composition of the vegetation so as to increase diversity and evenness of species. Keywords: Flora, Diversity, Biodiversity Park